(untitled) (Journal of Computational Mathematics, 1994)
In this paper, we present a new semi-discrete difference sheme for the KdV equation, which possesses the first four near-conserved quantities. The scheme is better than the past one given in [4], because its solution has a more superior estimation. The convergence and the stability of the new scheme are proved.